Analysis of safety of postoperative accelerated hypofractionated radiotherapy for patients with stage I-IIIA breast cancer - G. V. Afonin; I. A. Gulidov; Y. A. Ragulin; E. E. Beketov; S. V. Gamayunov; А. A. Zharikov; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал)
Aim: to conduct a comparative analysis of the safety of postoperative accelerated hypofractionated radiotherapy for patients with stage I-IIIA breast cancer.Material and Methods. From 2013 to 201, 316 patients with stage I-IIIA breast cancer were treated at A.F. Tsyb Medical Radiological Research Center. Postoperative accelerated hypofractionated radiotherapy at a single daily dose of 2.7 Gy to a total dose of 40.5 Gy was given to 223 patients. The control group patients received the conventional radiation therapy at 2 Gy per fraction to a total dose of 50 Gy (n=93). The quality of life of patients was evaluated using the questionnaire EQ-5D consisting of descriptive part and a visual analogue scale (EQ VAS).Results. The frequency of edema of the upper limb did not depend on the fractionation regimen. This complication occurred more often in cases with axillary radiotherapy (р<0.01) and in cases with radical mastectomy. No difference in the quality of life between the patient groups was found.Conclusion. Postoperative accelerated hypofractionated radiotherapy at 2.7 Gy per fraction to a total dose of 40.5 Gy is safe and can be used after both organ-sparing surgery and radical mastectomy. This radiotherapy regimen is more preferable than the conventional one due to the reduced treatment time. Axillary radiotherapy signifcantly increases the risk of lymphedema of the upper limb.